A Study on Role of Government support schemes in the growth of MSMEs in India - Singh, Ragini (Journal of Economics and Management, 2024)
This paper aims to explore the trends of budgetary allocation and utilization of MSMEs by Government and to know the various schemes launched by government of India for the growth of MSMEs. Tables and graphical methods have been used to know the trends of budgetary allocation by government for MSMEs. For these annual reports of MSMEs has been used hence, it is based on secondary data. The study finds that the government also allocated sufficient fund for MSME sector which shows increasing trend in the following year and the trend of utilisation was also increasing. The government has implemented several plans to encourage technology upgrades and modernization in infrastructure facilities as well as welfare of artisans and MSME workers. Enhancing the capacity of small and medium-sized businesses can propel economic growth through increased government budgetary allocation and usage for MSMEs. Innovation, increased competitiveness, and the development of jobs can all result from this help. Since MSMEs make up a large portion of the economy, they gain the most from additional finance, which boosts output and opens up new markets. This in turn creates a more dynamic and varied business climate, which benefits the economy as a whole Comprehending MSME programs guarantees that small and medium-sized businesses may effectively use accessible resources, financial assistance, and support services. MSMEs are now more equipped to expand, develop, and compete in the market thanks to this improved access.